NEXT 10 YEARS OF TEACHING AND LEARNING WITH TECHNOLOGY - Rashid, Pro. Abdul Rashid; Mohammad, Pro.Sanad Mohammad (International Journal of Multidisciplinary Research and Studies, 2021)
Integration of Knowledge, Communication, and Technology (ICT) will assist teachers to the worldwide requirement to switch traditional teaching methods with technology-based teaching and learning tools and facilities. In Malaysia, ICT is taken into account jointly of the most elements in transforming the country to future development. The Ministry of Education, through the newest Education Blueprint (2013-2025), insights the importance of technology-based teaching and learning into the schools’ national curriculum. This study aims to research teachers’ perceptions of the effectiveness of ICT integration to support the teaching and learning process within the classroom. A survey questionnaire was distributed randomly to a complete of 101 teachers from 10 public secondary schools in the national capital, Malaysia. The info for this quantitative research was analyzed for both descriptive and inferential statistics using SPSS (version 21) software. Findings indicate that teachers’ well-equipped preparation with ICT tools and facilities is one the most factors in the success of technology-based teaching and learning. . It absolutely was also found that professional development training programs for teachers also played a key role in enhancing students’ quality learning. For future studies, there’s a desire for consideration of other aspects of ICT integration especially from a management point of view concerning strategic planning and policymaking